State of the Art: Role of the Dendritic Cell in Induction of Allograft Tolerance - Rosen, Sarah J. (Transplantation, 2018)
Despite decades of research, the induction and maintenance of long-term allograft tolerance without immunosuppression remains an elusive goal in the field of solid organ and cell transplantation. Immunosuppressive medications frequently prevent or minimize acute cellular rejection but have failed to halt anti-donor antibody production and chronic organ rejection. Past efforts aimed at promoting lasting allograft tolerance have focused primarily on peripheral T cell depletion, augmentation of regulatory T cells, or induction via simultaneous hematopoietic stem cell transplantation and facilitation of donor chimerism. So far, none of these methods have led to consistently safe, feasible and long lasting donor organ acceptance. Over the course of the past 4 decades, the study of a unique population of antigen-presenting cells known as dendritic cells (DCs) has shown promise for breaking new ground in achieving indefinite allograft survival without immunosuppression and its associated adverse effects. In this review, we discuss the discovery and early investigations of DCs and chronicle some of the key studies demonstrating their role in transplantation, particularly in indirect allorecognition, the immunologic pathway thought to drive chronic rejection and perhaps tolerance induction.